Unraveling the impacts of ocean plastic pollution and strategies for effective mitigation - Karim, Sarker Mohammad Rezaul; Sulaiman, Zulkefly; Hamdani, Saiful Ahmad; Asif, Nayeem; Alam, Wahidul; Bhuiya, Simul; Islam, Naina (Konya: Umut Özkaya, 2023)
Plastic pollution in the ocean is a global environmental crisis with profound consequences for marine ecosystems, human societies, and the planet as a whole. This paper delves into the concept of plastic pollution in the ocean, emphasizing its pervasive and detrimental effects. It highlights the role of ocean as a source of sustenance, climate regulator, transportation route, and vital ecosystem provider. While oceans offer immense benefits, they face dire threats from plastic pollution. The harms of plastic pollution on marine life are explored, with a focus on ingestion, entanglement, and the introduction of harmful chemicals into the food chain. The adverse impact on water quality, sediment contamination, navigation, and various human activities are also discussed. Understanding the pathways of plastic leakage including land-based activities, stormwater runoff, marine-based industries, microplastic generation, shipping and maritime accidents, and even atmospheric deposition into the ocean is paramount. To mitigate plastic pollution, multifaceted approaches are required. Effective waste management and reduction of plastic production and consumption, including bans and restrictions on single-use plastics, offer tangible solutions. Extended Producer Responsibility (EPR) programs, improved recycling, and circular economy promotion are vital components of mitigation. Innovative cleanup technologies and the strengthening of international agreements and regulations are essential. This paper also offers policy recommendations, including the implementation of plastic reduction and bans, the enhancement of waste management systems, promotion of recycling and circular economy, and the enforcement of marine pollution prevention regulations. Education, research, and public awareness initiatives are equally critical in our collective efforts to combat plastic pollution in the ocean and safeguard the health of our marine ecosystems and our planet.